2003
DOI: 10.1093/ajcn/78.3.517s
|View full text |Cite
|
Sign up to set email alerts
|

Health benefits of fruit and vegetables are from additive and synergistic combinations of phytochemicals

Abstract: Cardiovascular disease and cancer are ranked as the first and second leading causes of death in the United States and in most industrialized countries. Regular consumption of fruit and vegetables is associated with reduced risks of cancer, cardiovascular disease, stroke, Alzheimer disease, cataracts, and some of the functional declines associated with aging. Prevention is a more effective strategy than is treatment of chronic diseases. Functional foods that contain significant amounts of bioactive components m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
1,181
1
44

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,812 publications
(1,247 citation statements)
references
References 29 publications
21
1,181
1
44
Order By: Relevance
“…Nevertheless, those assays were carried out using whole extracts instead of individual compounds. According to Liu (2003), additive and synergistic effects of phytochemicals in fruits and vegetables are responsible for their potent bioactive properties and the benefit of a diet rich in fruits and vegetables is attributed to the complex mixture of phytochemicals present in whole foods. This explains why no single antioxidant can replace the combination of natural phytochemicals to achieve the health benefits.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, those assays were carried out using whole extracts instead of individual compounds. According to Liu (2003), additive and synergistic effects of phytochemicals in fruits and vegetables are responsible for their potent bioactive properties and the benefit of a diet rich in fruits and vegetables is attributed to the complex mixture of phytochemicals present in whole foods. This explains why no single antioxidant can replace the combination of natural phytochemicals to achieve the health benefits.…”
Section: Resultsmentioning
confidence: 99%
“…These carotenoids have been found to exhibit anti-carcinogenic and anti-atherogenic properties as reviewed previously (Mayne, 1996;Palace et al, 1999), although it should be noted that randomized intervention trials with relatively high doses of individual carotenoids fed in isolation have shown an increased risk of some chronic diseases (Alpha-Tocopherol, Beta Carotene Cancer Prevention Study Group, 1994;Omenn et al, 1996). Nonetheless, the combined effects of increased levels of various carotenoids could have significant biological effects, as it has been suggested that several phytochemicals in combination may have a better protective effect than their individual parts (Liu, 2003). The increased plasma carotenoids, resulting mainly from the increased vegetables intake in vegetarians could also reflect elevated levels of 'other' phytochemicals in blood/body, which have not been measured in this study, including polyphenols, phyto-oestrogens and organosulfer compounds that are thought to have antioxidant as well as other biologically important properties (Kris-Etherton et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Mango is an excellent source of β-carotene (provitamin A carotenoid), vitamin C and polyphenolic compounds with traces of vitamins E, K and B. These bioactive compounds are good antioxidants and their daily intake in the diet has been related to prevention of degenerative processes such as cardiovascular diseases and cancer (Liu 2003). Thus, consumption of mango could provide significant amounts of bioactive compounds possessing antioxidant activity in the human diet.…”
Section: Introductionmentioning
confidence: 99%